Our inaugural issue - Jackson, Sarah (JCI Insight, 2016)
We are delighted to publish the first set of articles in JCI Insight, the newest peer-reviewed publication of the American Society for Clinical Investigation (ASCI), a nonprofit honor society for physician-scientists. In creating this journal, we sought to provide an expanded forum for a wide range of preclinical, translational, and clinical research that uncovers new insights into the basis of disease and therapeutic approaches. In selecting articles for JCI Insight, we place a strong emphasis on rigorous experimental methods and data reporting, which are truly the hallmark of publications in the JCI family. Like the research in the Journal of Clinical Investigation, all articles in JCI Insight are freely available from the moment of publication. ASCI is proud to continue this tradition of open access, which we believe to be a cornerstone of the dissemination of scientific findings.